Using Social Network Analysis to Monitor and Assess the Effectiveness of Knowledge Brokers at Connecting Scientists and Decision‐Makers: An Australian case study. (21st February 2017) - Cvitanovic, C.; Cunningham, R.; Dowd, A‐M.; Howden, S.M.; van Putten, E.I.
Abstract: Despite growing rhetoric regarding the potential benefits of using knowledge brokers in relation to environmental challenges and decision‐making processes, the evidence in support of such claims is mostly anecdotal. This is, in part, due to the lack of established methods to evaluate the effectiveness and efficiency of knowledge brokers. To address this gap we assess the utility of social network analysis (SNA) to evaluate the effectiveness of knowledge brokers in connecting scientists and decision‐makers. Specifically, using a case‐study approach, we undertake longitudinal SNA over a 12‐month period to evaluate the extent to which the knowledge broker developed networks between producers and users of knowledge across different organizations. We also undertook a qualitative survey of scientists ( n  = 29) who worked in the same organization as the knowledge broker to understand the extent to which the knowledge broker increased the impact of scientific research for decision‐making purposes. Results show that the knowledge broker developed an extensive stakeholder network of 192 individuals spanning over 30 organizations. The results of the SNA found that over time this network increased in density and became more cohesive, both key elements underpinning successful knowledge exchange. Furthermore, the qualitative survey found that the knowledge broker also had a positive impact in other ways, including helping researchers understand the operating environments within decision‐making agencies and the best approaches for engaging with specific decision‐makers. Thus, this study demonstrates the value of SNA for evaluating knowledge brokers and provides empirical support for the use of knowledge brokers in the environmental sector. Copyright © 2017 John Wiley & Sons, Ltd and ERP Environment